Analysis Of Factors Hindering Online Entrepreneurship Among Students: A Study Of Perceptions Of Financial Risk And Lack Of Digital Skills - Vina Mafaza; Seviani Najiyah; Fina Nikmatul Kamelia; Muntaqo Fadli (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2026)
The development of the digital ecosystem has created broad opportunities for students to engage in online entrepreneurship. However, this high level of interest has not been fully accompanied by adequate readiness to start a business. This study aims to analyze the inhibiting factors of online entrepreneurship among students, particularly perceptions of financial risk and the lack of digital skills. The research employed a quantitative approach with a descriptive-analytical method. Data were collected through an online questionnaire distributed to students of the Faculty of Tarbiyah and Teacher Training at K.H. Abdurrahman Wahid State Islamic University Pekalongan using purposive sampling. The data were analyzed descriptively using mean scores and percentages. The findings indicate that despite students’ high interest in online entrepreneurship, significant barriers remain, including limited capital, anxiety in financial management, and insufficient digital skills, especially in content creation and social media marketing strategies. In addition, non-technical factors such as limited time due to academic demands and fear of failure also hinder students from starting online businesses. This study highlights the importance of higher education institutions in providing practical digital skills training, financial management assistance, and entrepreneurial mindset development to encourage sustainable student engagement in online entrepreneurship.